Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Discover in-depth answers to your questions from a wide network of experts on our user-friendly Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Let's solve each equation step by step.
### Solving for [tex]\( n \)[/tex] in the equation [tex]\( 3(2n + 5) = 2n - 9 \)[/tex]:
1. Expand the left side of the equation:
[tex]\[ 3(2n + 5) = 3 \cdot 2n + 3 \cdot 5 = 6n + 15 \][/tex]
So, the equation becomes:
[tex]\[ 6n + 15 = 2n - 9 \][/tex]
2. Move all terms involving [tex]\( n \)[/tex] to one side of the equation by subtracting [tex]\( 2n \)[/tex] from both sides:
[tex]\[ 6n + 15 - 2n = 2n - 9 - 2n \][/tex]
This simplifies to:
[tex]\[ 4n + 15 = -9 \][/tex]
3. Isolate the term with [tex]\( n \)[/tex] by subtracting 15 from both sides:
[tex]\[ 4n + 15 - 15 = -9 - 15 \][/tex]
This further simplifies to:
[tex]\[ 4n = -24 \][/tex]
4. Solve for [tex]\( n \)[/tex] by dividing both sides by 4:
[tex]\[ n = \frac{-24}{4} = -6 \][/tex]
Thus, the value of [tex]\( n \)[/tex] is [tex]\(-6\)[/tex], which corresponds to choice (b).
### Solving for [tex]\( m \)[/tex] in the equation [tex]\( \frac{5m}{3} + 5 = m + 7 \)[/tex]:
1. Eliminate the fraction by multiplying the entire equation by 3:
[tex]\[ 3 \left(\frac{5m}{3} + 5 \right) = 3 (m + 7) \][/tex]
This simplifies to:
[tex]\[ 5m + 15 = 3m + 21 \][/tex]
2. Move all terms involving [tex]\( m \)[/tex] to one side of the equation by subtracting [tex]\( 3m \)[/tex] from both sides:
[tex]\[ 5m + 15 - 3m = 3m + 21 - 3m \][/tex]
This simplifies to:
[tex]\[ 2m + 15 = 21 \][/tex]
3. Isolate the term with [tex]\( m \)[/tex] by subtracting 15 from both sides:
[tex]\[ 2m + 15 - 15 = 21 - 15 \][/tex]
This further simplifies to:
[tex]\[ 2m = 6 \][/tex]
4. Solve for [tex]\( m \)[/tex] by dividing both sides by 2:
[tex]\[ m = \frac{6}{2} = 3 \][/tex]
Therefore, the value of [tex]\( m \)[/tex] is [tex]\( 3 \)[/tex], which corresponds to choice (a).
### Solving for [tex]\( n \)[/tex] in the equation [tex]\( 3(2n + 5) = 2n - 9 \)[/tex]:
1. Expand the left side of the equation:
[tex]\[ 3(2n + 5) = 3 \cdot 2n + 3 \cdot 5 = 6n + 15 \][/tex]
So, the equation becomes:
[tex]\[ 6n + 15 = 2n - 9 \][/tex]
2. Move all terms involving [tex]\( n \)[/tex] to one side of the equation by subtracting [tex]\( 2n \)[/tex] from both sides:
[tex]\[ 6n + 15 - 2n = 2n - 9 - 2n \][/tex]
This simplifies to:
[tex]\[ 4n + 15 = -9 \][/tex]
3. Isolate the term with [tex]\( n \)[/tex] by subtracting 15 from both sides:
[tex]\[ 4n + 15 - 15 = -9 - 15 \][/tex]
This further simplifies to:
[tex]\[ 4n = -24 \][/tex]
4. Solve for [tex]\( n \)[/tex] by dividing both sides by 4:
[tex]\[ n = \frac{-24}{4} = -6 \][/tex]
Thus, the value of [tex]\( n \)[/tex] is [tex]\(-6\)[/tex], which corresponds to choice (b).
### Solving for [tex]\( m \)[/tex] in the equation [tex]\( \frac{5m}{3} + 5 = m + 7 \)[/tex]:
1. Eliminate the fraction by multiplying the entire equation by 3:
[tex]\[ 3 \left(\frac{5m}{3} + 5 \right) = 3 (m + 7) \][/tex]
This simplifies to:
[tex]\[ 5m + 15 = 3m + 21 \][/tex]
2. Move all terms involving [tex]\( m \)[/tex] to one side of the equation by subtracting [tex]\( 3m \)[/tex] from both sides:
[tex]\[ 5m + 15 - 3m = 3m + 21 - 3m \][/tex]
This simplifies to:
[tex]\[ 2m + 15 = 21 \][/tex]
3. Isolate the term with [tex]\( m \)[/tex] by subtracting 15 from both sides:
[tex]\[ 2m + 15 - 15 = 21 - 15 \][/tex]
This further simplifies to:
[tex]\[ 2m = 6 \][/tex]
4. Solve for [tex]\( m \)[/tex] by dividing both sides by 2:
[tex]\[ m = \frac{6}{2} = 3 \][/tex]
Therefore, the value of [tex]\( m \)[/tex] is [tex]\( 3 \)[/tex], which corresponds to choice (a).
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.